EVALUATING PRIMARY EDUCATION IN KHYBER PAKHTUNKHWA UNDER THE GOVERNMENTS OF ANP AND PTI - Yasir Khan; Dr. Fayyaz Ali; Asif Khan; Misbah Hayat; Zahid Nawaz Khan (International Journal of Contemporary Issues in Social Sciences, 2024)
This research comparatively analyzes the primary education in Khyber Pakhtunkhwa (KP) province taking into account the Awami National Party (ANP) government (2008-2013), and the Pakistan Tahreek-e-Insaf (PTI) government (2013-2018). The study investigates the phenomenon by exploring three key variables, i.e., the number of government schools, student enrollment, and teaching staff. The data was acquired from the KP Bureau of Statistics. Both regression analysis and observation of the average value of the variables during ANP and PTI tenures are made to help better understand their comparative performance. As the data shows, the era of ANP, from 2008- 2013, included general stability with mild and moderate changes in government schools, student enrollment, and teacher staff. In contrast, the following PTI government’s tenure observed significant changes, marked by a notable increase in the number of government schools, an increase in student enrollments, and considerable growth in teaching staff. The results and discussion highlight the distinct trends and policy interventions during the two eras, emphasizing a shift in focus and investment in primary education under the PTI government. The research concludes with policy recommendations, emphasizing the need for a robust monitoring and evaluation framework, targeted infrastructure development, and strategic interventions to address gender-specific variations in educational outcomes.